CFD modeling of liquid-metal heat pipe and hydrogen inactivation simulation. (15th December 2022) - Wang, Xiaoyuan; Shi, Yuwen; Liu, Tiancheng; Wang, Shuai; Wang, Kai; Chen, Haijun; Wang, Yifeng; Zhu, Yuezhao
Highlights: Development of a comprehensive CFD model for liquid-metal heat pipes. Model validation by heat output and temperature distributions in steady state. CFD investigation on effects of hydrogen permeation in a sodium heat pipe. Hydrogen migration and distribution along with phase change of sodium. Further structure optimization suggestions for the hydrogen window. Abstract: The use of hydrogen window is a potential way for liquid metal heat pipes (LMHPs) to avoid hydrogen inactivation when operated in a hydrogen-containing atmosphere. To reveal the effects of hydrogen permeation on heat transfer in LMHPs in a visual way, we develop a comprehensive CFD model in this work for the first time, and experimental tests are also carried out for model validation. The experimental results show that the top end of an LMHP reduces to below 400 ℃ after hydrogen inactivation, when the heating temperature of the evaporator is maintained at 950 ℃. It takes about 150 min for the LMHP to recover performance by flushing its hydrogen window with nitrogen controlled at 50 mL/min. The CFD model is demonstrated reliable by comparing the predicted heat output and temperature distribution with the experimental results in steady state. The CFD model is capable of reproducing the liquid up-throwing phenomenon, and revealing the impact of hydrogen-buffer formation on heat transfer. In addition, the hydrogen migration along with the returning condensate leads to the formation of a gas blanket covering the inner surface in the condenser, which has a negative effect on the heat transfer as well.